Visualization of Traceability Models with Domain-speciﬁc Layouting - Hegedüs, Ábel; Ujhelyi, Zoltán; Ráth, István; Horváth, Ákos (Electronic Communications of the EASST, 2011)
Traceability models are often used to describe the correspondence between source and target models of model transformations. Although the visual representation of such models are important for transformation development and application, mostly ad-hoc solutions are present in industrial environments. In this paper we present a user interface component for visualizing traceability models inside transformation frameworks. As generic graph visualization methods fail to emphasize the underlying logical structure of our model, we used domain-speciﬁc layouts by customizing generic graph layout algorithms with data from the metamodels used during the transformation. This approach was evaluated, among others, with the traceability models generated by a BPEL veriﬁcation transformation, which serves as our running example.